The good house [compact disc, unabridged] : a novel - Leary, Ann (Macmillan Audio, 2012)
The Good House tells the story of Hildy Good, who lives in a small town on Boston's North Shore. Hildy is a successful real-estate broker, good neighbor, mother, and grandmother. She's also a raging alcoholic. She has also fooled herself into thinking that moderation is the key to her drinking problem. As if battling her demons wasn't enough to keep her busy, Hildy soon finds herself embroiled in the underbelly of her New England town, a craggy little place that harbors secrets.